Foundation ownership and sustainability - Schröder, David; Thomsen, Steen (Journal of Corporate Finance, 2025)
Concerns about the sustainability of contemporary capitalism have inspired a search for organizational forms that are more concerned with solving environmental and social problems. We examine whether one such model – foundation ownership – where a non-profit foundation owns and controls business companies, is associated with better sustainability outcomes. We hypothesize that foundations prioritize environmental and social objectives over profit maximization, resulting in stronger ESG performance in the companies they own. Using data on listed foundation-owned companies over the period 2003–2020 matched with control groups by firm size and industry, we find that foundation-owned firms have higher environmental, social, and governance (ESG) performance, particularly in the environmental and social dimensions. They maintained ESG activities during the financial crisis and committed to more significant emission reductions in the post-Paris Agreement period. Collectively, our findings highlight the potential of purposeful ownership in promoting corporate sustainability.